Maydisone, a novel oxime polyketide from the cultures of Bipolaris maydis. Issue 1 (22nd December 2021) - Tran, Thi-Minh-Dinh; Nguyen, Van-Kieu; Duong, Thuc-Huy; Tran, Thanh-Nha; Nguyen, Ngoc-Hong; Devi, Asshaima Paramita; Chavasiri, Warinthorn; Dinh, Minh-Hiep; Tran, Nguyen-Minh-An; Sichaem, Jirapast
Abstract: A novel oxime polyketide, maydisone (1 ), along with two known compounds, 7-hydroxy-2, 5-dimethylchromone (2 ) and 2, 5-dimethylbenzoic acid (3 ) were isolated from the cultures of Bipolaris maydis . Their structures were identified by the application of NMR and MS data analyses and comparison with previous reports. Compound 1 showed the most powerful inhibition of α -glucosidase, with an IC50 value of 68.30 ± 0.83 µM. Graphical Abstract: UF0001